Technological capabilities and export success in Asia - Ernst, Dieter 1942-; Ganiatsos, Tom (Thomas George) 1936-; Mytelka, Lynn Krieger (Routledge series in the growth economies of Asia, 1998)
This book shows how cheap labour, combined with currency devaluation is no longer sufficient for export success, through a series of case studies of textile and garment and electronics industries in five Asian economies.